WR-2721 (amifostine, ethyol®) prevents motor and morphological changes induced by neonatal X-irradiation - Guelman, Laura Ruth (2003)
Neonatal X-irradiation induces permanent abnormalities in cerebellar cortex cytoarchitecture and neurochemistry, as well as impairment in motor gait. The aim of the present work was to examine the potential protective properties of WR-2721 (Amifostine, Ethyol®), a free radical scavenger, against the above mentioned alterations by using a previously described neuroprotection assessment protocol. Pre-irradiation treatment with amifostine was effective in partially preventing the cerebellar morphological damage and the motor gait impairment induced by ionizing radiation. No changes in cerebellar noradrenaline (NA) levels were detected in amifostine-treated  irradiated animals. These results suggest that it is possible to counteract radiation-induced damage in the cerebella and motor gait of neonatal rats through oxygen free radical scavenger administration prior to irradiation. The presence of the agent before the injury occurs, favors the efficacy of amifostine neuroprotective activity. Clinical implications of this model are related to the daily exposure of many people to different sources of radiation (accidental, diagnostical or therapeutical).